CLINICAL SPECTRUM OF COGNITIVE DISORDERS (Multidisciplinary Journal of Science and Technology, 2023)
A retrospective cohort study was conducted on the results of a comprehensive examination and treatment of 87 patients with COVID-19. In patients at the time of hospitalization with COVID-19, all studied markers of coagulation activity were statistically significantly different from the reference interval, which indicated activation of the procoagulation potential. In the group of female patients, these indicators were more pronounced. A CT study found that the percentage of lesions in both lungs was significantly higher in females compared to male patients.